Respuesta :

Answer:

Proved!

Step-by-step explanation:

We know  that,

[tex]\bigstar\; \boxed{\sf {Area\; of\; triangle= \dfrac{1}{2} \times Base \times Height\;\dfrac{1}{2} \times Base \times Height}}[/tex]

So,

[tex]\it Area\; of\; triangle, ABD= \dfrac{1}{2} \times BD \times AN12\times BD \times AN[/tex]

And,

[tex]\it Area\; of\;triangle\;ADC= \dfrac{1}{2} \times DC \times AN =12 \times BD \times AN\;\dfrac{1}{2} \times DC \times AN = 12 \times BD \timesAN[/tex]

(As we know BD  =  DC )

So,

Area of triangle ABD  = Area of triangle ADC                                  

(Hence proved)

[tex]\rule{300}{1.5}[/tex]

Note :

Kindly Post/Attach figure If question is related to figure.

I have Attach the figure now!

Thanks!

Ver imagen BrainlyTreasure